2009
DOI: 10.1021/ol902402v
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Nucleophilic Addition to Pyridinium Salts: A New Route to Substituted Dihydropyridones

Abstract: The regioselective addition of nucleophiles to pyridinium salts generates an intermediate enol-ether, which can be hydrolyzed in situ to provide a range of dihydropyridones. Certain Grignards have shown inherent differences in the regioselectivity of addition to these salts, and this difference can be tuned to give single regioisomeric addition products. The dihydropyridone products can be further manipulated in many ways using standard transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…24 Accordingly, we have demonstrated that the nucleophilic addition of various Grignard reagents to pyridinium salts provides selectively either the C2 or C6 addition products, depending on the reagent employed (Scheme 9). 25 We decided to test this methodology to the syntheses of piperidine-containing alkaloids named the cylindricines. The cylindricines were isolated by Blackman et al between 1993 and 1995 from the ascidian Clavelina cylindricia.…”
Section: Nucleophilic Addition To Pyridinium Saltsmentioning
confidence: 99%
“…24 Accordingly, we have demonstrated that the nucleophilic addition of various Grignard reagents to pyridinium salts provides selectively either the C2 or C6 addition products, depending on the reagent employed (Scheme 9). 25 We decided to test this methodology to the syntheses of piperidine-containing alkaloids named the cylindricines. The cylindricines were isolated by Blackman et al between 1993 and 1995 from the ascidian Clavelina cylindricia.…”
Section: Nucleophilic Addition To Pyridinium Saltsmentioning
confidence: 99%
“…Initial studies involved benzyl iodide and homoallyl triflate since removal of the protecting groups would be easy by use of palladium-catalyzed hydrogenolysis or palladium-catalyzed deallylation [6,14], respectively. The synthesis of the pyridinium salts again started from the di-substituted pyridine 6 (Scheme III) [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Other electron-rich aryl protecting groups such as 4-methoxybenzyl and 3,4-dimethoxybenzyl protecting groups were also investigate by Donohoe during preparation of pyridinium salts 9 and 10, respectively (Scheme IV) [7][8][9][15][16]. The synthesis of paramethoxybenzyl iodide (PMB-I) started from commercially available 4-methoxybenzyl alcohol while the synthesis of 3,4-dimethoxybenzyl bromide (DMB-Br) started from commercially available 3,4-dimethoxybenzaldehye [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…A facile route to functionalized dihydropyridones has been developed via formal [5C+1N] of α-alkanoyl ketene-(S,S)-acetals with aliphatic amines [17]. In addition, partial reduction of pyridinium salts had also been used for their synthesis [18]. Enantiopure dihydropyridones were synthesized from intramolecular hydride addition to pyridinium salts [19].…”
Section: Introductionmentioning
confidence: 99%